Off-Label Uses of Anti-TNF Therapy in Three Frequent Disorders: Behçet's Disease, Sarcoidosis, and Noninfectious Uveitis. (31st July 2013) - Sánchez-Cano, Daniel; Callejas-Rubio, José Luis; Ruiz-Villaverde, Ricardo; Ríos-Fernández, Raquel; Ortego-Centeno, Norberto
Abstract : Tumoral necrosis factor α plays a central role in both the inflammatory response and that of the immune system. Thus, its blockade with the so-called anti-TNF agents (infliximab, etanercept, adalimumab, certolizumab pegol, and golimumab) has turned into the most important tool in the management of a variety of disorders, such as rheumatoid arthritis, spondyloarthropatties, inflammatory bowel disease, and psoriasis. Nonetheless, theoretically, some other autoimmune disorders may benefit from these agents. Our aim is to review these off-label uses of anti-TNF blockers in three common conditions: Behçet's disease, sarcoidosis, and noninfectious uveitis. Due to the insufficient number of adequate clinical trials and consequently to their lower prevalence compared to other immune disorders, this review is mainly based on case reports and case series.